Ala®sil chemical characterization and toxicity evaluation: an example of the need for the Medical Device Regulation 2017/745 - Andrés-Iglesias, Cristina; Fernandez-Bueno, Ivan; Pastor-Idoate, Salvador; Coco-Martin, Rosa M.; Pastor, J. Carlos (Frontiers in Pharmacology, 2024)
Introduction: Ala®sil infusion was on the market for clinical use under the Medical Devices Directive (MDD) 93/42/EEC as an irrigating solution based on polydimethylsiloxane (PDMS). The product was withdrawn in 2016, and to the best of our knowledge, it did not cause any health damage. Methods: A bibliographic review and experimental analysis were conducted to evaluate whether this CE-marked product could have been used in patients under the current Medical Device Regulation (MDR) 2017/745. Analytical results from gas chromatography–mass spectrometry (GC-MS) and matrixassisted laser desorption ionization (MALDI) were performed. Citotoxicity studies were also carried out. Results: Only one study related to Ala®sil clinical use was found, describing a pilot series of five patients. The authors rated the product as not helpful in three out of the five cases for internal searching of retinal breaks and in four out of the five cases for drainage of subretinal fluid. No other scientific papers or documentation was found regarding Ala®sil’s safety. Nevertheless, the product was introduced in the market after achieving the CE marking. GC-MS and MALDI showed that the polymer has a low molecular weight of 1,000 g/mol. Several linear and cyclic low-molecular-weight components (LMWCs) were identified as impurities ranging from L3 to D8, with a molecular weight below 600 g/mol. The Ala®sil sample was found to be cytotoxic after 24 h of cell culture but non-cytotoxic after 72 h, probably due to the cellular regeneration capacity of an immortalized cell line. Tissular cytotoxicity revealed an increased apoptosis rate but without morphological modifications. Discussion: Although Ala®sil cannot be classified as cytotoxic, this substance appears to increase retinal cell death processes. This study supports the notion that the MDDwas not functioning adequately to ensure the safety of medical devices. However, the current MDR 2017/745 imposes stricter standards to prevent the commercialization of medical devices without high-quality preclinical and clinical information, as well as precise clinical verification for their use, information not available for Ala®sil infusion.